Simulation of methane hydrate grain dissociation within a porous matrix - Lyubimova, Tatiana Petrovna; Tsiberkin, Kirill Borisovich (Computational Continuum Mechanics, 2013)
The results of numerical simulation of the methane hydrate grain dissociation within a water-saturated porous matrix in a linear approximation at small perturbations of thermodynamic equilibrium of phases are presented. The qualitative behavior of the system in this approximation is shown to be reliable. Quantitative estimates of intensity of dissociation and lifetime of methane hydrate grains are obtained.
Keywords: porous medium; filtration; methane hydrates; numerical modeling